Go-go girls of the apocalypse eaudiobook - Gischler, Victor (Recorded Books Inc., 2015)
Edgar Award nominee Victor Gischler "specializes in morbid humor, dark sarcasm, and comic noir, complete with violence and mayhem" (Library Journal). Go-Go Girls of the Apocalypse picks up 10 years after the end of the world. Former insurance salesman Mortimer Tate leaves his secluded cabin and discovers a desolate landscape complete with cowboys, bandits, and cannibals, where the only traces of civilization are found at Joey Armageddon's Sassy-a-Go-Go club. "Compulsively readable."-Booklist